Liz Henty, Exploring Archaeoastronomy: A History of Its Relationship with Archaeology and Esotericism. (13th February 2023) - Hutton, Ronald
Abstract : Liz Henty, Exploring Archaeoastronomy: A History of Its Relationship with Archaeology and EsotericismOxford: Oxbow Books, 2022, 278pp, b/w and colour illus. ISBN 978 1 78925 786 1.